Analisis Ikonisitas Visual karakter Utama Pada Film The Watchmen - Saptodewo, Febrianto; Qeis, Muhammad Iqbal; Sidhartani, Santi; Anto, Puji (ULTIMART Jurnal Komunikasi Visual, 2024)
Film has become a powerful medium for introducing complex and deep characters to its audience. This research adopts an approach in the field of visual communication design to explore how the main characters in the film "Watchmen" can be deepened through various visual and narrative elements. Focusing on six main characters: Dr. Manhattan, Ozymandias, Rorschach, Silk Spectre, Nite Owl, and The Comedian, this study analyzes how the visual analysis can help strengthen the characters' identities and development in creating a cohesive visual narrative by using the visual iconicity approach. Through this approach, the research not only aims to understand the characters in the context of the film but also to explore how visual communication design can depict the psychological and emotional dimensions of characters more deeply. The results of this research are expected to provide new insights into understanding the influence of visual communication design on character narrative in the context of modern cinema. Keywords: character design; visual analysis; visual iconicity; watchmen